Effective Analysis of English Learning in English Courses - Anak Agung Gede Raka Wahyu Brahma; Maria Osmunda Eawea Monny (PT PUSTAKA CENDEKIA GROUP, 2026)
English is a foreign language taught as a course in Indonesia. English strongly supports courses in their respective fields, such as technology. In reality, both lecturers and students still face numerous challenges during the learning process. Various responses can be found in class regarding these issues, particularly regarding student attitudes during the learning process, student learning outcomes, and participation in group activities. This study aims to describe the difficulties and obstacles faced by students in learning English and the factors that contribute to them. This study used a qualitative approach using questionnaires, observations, and video recordings. Data analysis was conducted through three methods: data reduction, data presentation, conclusion drawing, and verification. The results indicate that the study subjects experienced various difficulties in learning English. This occurs due to varying levels of English proficiency. Keywords: learning difficulties, competence, English, learning process, learning outcomes